A series of s-block (Ca, Sr and Ba) metal–organic frameworks: synthesis and structure–property correlation. Issue 6 (21st January 2016) - Asha, K. S.; Makkitaya, Madhuri; Sirohi, Anshu; Yadav, Lalit; Sheet, Goutam; Mandal, Sukhendu
Abstract : Structure–property correlation of alkaline earth metal ions (Ca, Sr and Ba) and tritopic ligand based Metal–Organic Framework structures. Abstract : A series of metal–organic frameworks based on alkaline earth metal ions (Ca, Sr and Ba) and 1, 3, 5-benzenetribenzoic acid (BTB) have been synthesized and characterized. These are [H2 N(CH3 )2 ][Ca7 (BTB)5 (H2 O)8 (DMF)4 ]·4H2 O (1 ), [H2 N(CH3 )2 ]2 [Sr5 (H2 O)6 (BTB)4 ] (2 ) and [H2 N(CH3 )2 ][Ba(H2 O)(BTB)] (3 ). All the structures are three-dimensional in nature with different secondary building units. Compound1 contains one-dimensional Ca–O–Ca zigzag chains while compound2 contains Sr5 O28 pentameric clusters and compound3 contains one-dimensional Ba–O–Ba chains. Both compounds1 and3 form (3, 6)-net connectivity while compound2 forms (3, 12)-net connectivity. Optical band gap energy measurements show that compound1 (2.65 eV) has low band gap energy compared to2 (3.22 eV) and3 (3.32 eV). This variation in band gap energy may be due to the difference in structural arrangement. Compound3 crystallizes in a non-centrosymmetric space group ( Pna 21 ), which belongs to the polar point group C 2v . This compound displays a strong SHG response and good ferroelectric and piezoelectric properties.